Incidências da vergonha na contemporaneidade - Anamaria Batista Nogueira (2016)
This work demonstrates a theoretical and clinical investigation of the incidence of the affection of shame in most recent times (at the beginning of the 21st century). As such we start from the cultural concept of shame nowadays and also during morally defining moments of history in order to identify possible changes in its form of expression. We support the hypothesis that shame is inherent to ones subjective constitution independent of the moral issue. Firstly, we investigate the approach to shame in some areas of knowledge such as Philosophy, Psychology and Sociology, which work as a counterpoint to the psychoanalytical theory, where we take as the main theoretical support the concepts of the ideal ego and the superego. Secondly, we studied the theme of shame into the theory and clinic of Sigmund Freud in order to identify a possible specificity for shame based on the theory of affection and repression that in turns corroborate our proposal. Lastly, we use the connection between the gaze, the shame and the Other present in Jacques Lacan work which is not only supported by the author but also by fellow psychoanalysts such as Jacques-Alain Miller and Éric Laurent whilst addressing the theme of shame and the Law of the Father existent in contemporary times, without ignoring 21st century evidences of shame in a clinic environment.